A History of the United Jewish Appeal - Raphael, Marc Lee (Brown Judaic Studies, 2020)
The United Jewish Appeal (UJA) was the primary Jewish philanthropic umbrella organization until it was combined with another philanthropic organization in 1999. Using original archival research, this volume traces the history of the UJA from its origins to 1982.